Changes in the surface topography and element proportion of clinically failed SLA implants after in vitro debridement by different methods. Issue 3 (10th January 2021) - Tong, Zian; Fu, Renjie; Zhu, Weijun; Shi, Jue; Yu, Mengfei; Si, Misi
Abstract: Objective: To evaluate the surface topography and element proportion changes in clinically failed implants after different modalities in vitro debridement and to compare the cleaning effect of different method combinations. Material and Methods: Thirty clinical failed implants were treated by different debridement methods in vitro as follows: Group 1: physiologic saline irrigation; Group 2: glycine powder air polishing; Group 3: glycine powder air polishing + ethylenediaminetetraacetic acid (EDTA); Group 4: polyetheretherketone (PEEK) tip ultrasonic scaling; and Group 5: PEEK tip ultrasonic scaling + EDTA. The relative contaminated area reduction (RCAR), visual analogue scale (VAS, the higher value means, the better cleaning effect) and surface roughness were assessed using scanning electron microscopy ( SEM ), stereoscopic microscopy (SM) and white light interferometry (WLI). Surface chemistry was determined by energy dispersive spectroscopy (EDS). Results: Group 4 and Group 5 showed higher RCARs (82.90%, 82.89%), VAS scores (2.61, 2.33) and roughness reductions (−0.85 μm, −1.80 μm). Group 3 attained the highest decrease of C% (carbon, −26.67%), O% (oxygen, −13.71%) and N % (nitrogen, −5.66%), and the highest increase of Ti% (titanium, 49.67%). PEEK remnants were detected on the implant surface of Groups 4 and 5. Conclusion: Within the limitation of the present in vitro design, PEEK tip ultrasonic scaling was more effective in eliminating visible contamination, while glycine powder air polishing combined with EDTA treatment was more conducive to expose the original surface element distribution. Both methods have their own advantages in decontamination, but none of them could reconstruct the surface as the pristine implant.